Rice Grain Grading Classification Based On Perimeter Using Moore-Neighbor Tracing Method - Piramli, Muhamad Marzuki; Abdul Rahman, Ahmad Fadzli Nizam; Abdullah, Siti Fairuz (Penerbit Universiti, UTeM, 2016)
-